Apocalypse ; Vision of the Virgin ; Pabasa, Senakulo [videorecording] - Lazaro, Cheche (Quezon City Probe Production, 1990)
A report on foretelling the future based on published prophecies. Marian devotees claim the Blessed Virgin Mary has appeared miraculously in Batangas, Quezon City and Loakan, Baguio City. The team looks into some explanations on the apparitions. The team also looks at traditional Filipino Holy Week practices.
Apocalypse (12 min.) -- Vision of the Virgin (18 min.) -- Pabasa, Senakulo (19 min.)
VHS.
Keywords: Mary, Bleesed Virgin, saint -- Apparitions and miracles -- Philippines; Regression (Civilization).; End of the world; Prophecies; Religious dramas; Lent -- Philippines; Passion plays -- Philippines; Processions, religious -- Philippines; Holy Week -- Philippines